Bioethical Competencies in Hydrotherapy Practice: the view of international Aquatic Therapists - Marcone-Dapelo, Pamela; Dapelo Pellerano, Bianca (Acta Bioethica, 2025)
Objectives: The main objective is to explore the bioethical competencies that aquatic therapists consider important in hydrotherapeutic practice at an international level. Methodology: qualitative of a phenomenological type with an intentional and opinionated sampling. The sample is made up of 14 international senior aquatic therapists, who participate in semi-structured interviews in an online modality. Thematic categorical content analysis is carried out with the support of the Atlas Ti version 23 software. Results: A comprehensive understanding of bioethical competencies is developed from a personalist perspective, highlighting the following components: bioethical sensitivity, bioethical knowledge, bioethical practice, and bioethical relationships. Emerging categories include the need for accredited training, academic integrity, accessibility gaps, and a holistic view of health. Conclusions: The existence of bioethical competencies consistent with the personalist approach, the principle of vulnerability, and values such as respect, humility, and honesty is evident. This highlights the need to develop bioethical competencies related to respect, responsibility, and integrity. A challenge is posed to reach a consensus on bioethical competencies that, from a holistic health perspective, can contribute to the validation and regulation of widespread aquatic practice at an international level.